MORAL INTENSITY AND ETHICAL ANALYSIS IN ACCOUNTING DECISION MAKING - Yusnaini Yusnaini; Eka Meirawati (AKUNTABILITAS, 2023)
Theoretically there are four stages in ethical decision making, namely identification of an ethical dilemma, ethical judgment, ethical intention, and ethical action. This study examines the relationship between perceived moral intensity and the first three stages of the ethical decision-making process for accounting students. This study uses an experimental design that uses four business scenarios. This study examines three stages in the ethical decision-making process and provides additional support for the role of moral intensity in ethical decision-making. The results of empirical testing at least partially support all the hypotheses developed in this study. Ethical identification was significantly related to ethical judgment and ethical intention of the four scenarios and ethical judgment was significantly related to ethical intention of the four scenarios. The two dimensions of moral intensity are differently related to the stages of the ethical decision-making process with social consensus emerging as the most important component of moral intensity